Will the argues between an employee and an employer come to the end? - G. D. Tsesarskaya (Бюллетень сибирской медицины)
In the article the question of regulation of the relations between the employer and employers is discussed. With the aim to define these relations there was established, inner Thesis about the office inventions in Siberian State Medical University.